Measurement of software maintenance from user satisfaction perspective: a case study - Helmee, Nurdhiya Hazwani; Rosli, Rozilah; Koh, Tieng Wei; Sharif, Khaironi Yatim (Institute of Research Engineers and Doctors, 2015)
The importance of software maintenance in a software development environment is a long term and continuous activity for improvement. The service quality of the software maintenance provided in which involving helpdesk, programmer and software analyst should be measured in order to satisfy users who use the software. In this paper, we propose a software measurement program for product improvement in order to maximize the user satisfaction where one government agency is selected as our case study. Our measurement plan is based on Goal Question Metric (GQM) approach. Results from this measurement program with some meaningful quantitative analysis has given an achievable roadmap for the organization to plan for next improvement activities toward their goals.